Kesalahan berbahasa pada berita Liputan6.com dan implikasinya terhadap pembelajaran bahasa Indonesia SMA fase F - Faridhatun Nikmah faridhatun nikmah; Nur Aini Zulfah; Siti Nur Janah (IRecall Journal, 2025)
The purpose of this study is to describe language errors in the field of linguistics and spelling. In the field of linguistics, it specializes in the fields of syntax and morphology. The method of this research is descriptive qualitative by describing the form of error data in accordance with the data obtained. The data source used in this study is the April 2019 edition of Liputan6.com news document. Data collection is done by reading, taking notes, classifying, and analyzing. The results of language error analysis include linguistic errors and spelling mistakes. Linguistic errors include, (1) morphological errors consisting of 30 errors, (2) syntactic errors consisting of 14. Spelling errors include, (1) writing italics reaching 30, (2) writing combined words reaching 3, (3) using marks comma reaches 140, (4) the use of quotation marks reaches 20, and (5) the use of prepositions reaches 3. From the results of the most dominant language error analysis found is an error in spelling in the use of commas.